The Evolution of Human Vocal Emotion. (January 2021) - Bryant, Gregory A.
Vocal affect is a subcomponent of emotion programs that coordinate a variety of physiological and psychological systems. Emotional vocalizations comprise a suite of vocal behaviors shaped by evolution to solve adaptive social communication problems. The acoustic forms of vocal emotions are often explicable with reference to the communicative functions they serve. An adaptationist approach to vocal emotions requires that we distinguish between evolved signals and byproduct cues, and understand vocal affect as a collection of multiple strategic communicative systems subject to the evolutionary dynamics described by signaling theory. We should expect variability across disparate societies in vocal emotion according to culturally evolved pragmatic rules, and universals in vocal production and perception to the extent that form–function relationships are present.